Synthesis of Diblock copolymer poly-3-hydroxybutyrate -block-poly-3-hydroxyhexanoate [PHB-b-PHHx] by a β-oxidation weakened Pseudomonas putida KT2442 - Tripathi Lakshmi; Wu Lin-Ping; Chen Jinchun; Chen Guo-Qiang (Microbial Cell Factories, 2012)
Abstract Background Block polyhydroxyalkanoates (PHA) were reported to be resistant against polymer aging that negatively affects polymer properties. Recently, more and more attempts have been directed to make PHA block copolymers. Diblock copolymers PHB-b-PHHx consisting of poly-3-hydroxybutyrate (PHB) block covalently bonded with poly-3-hydroxyhexanoate (PHHx) block were for the first time produced successfully by a recombinant Pseudomonas putida KT2442 with its β-oxidation cycle deleted to its maximum. Results The chloroform extracted polymers were characterized by nuclear magnetic resonance (NMR), thermo- and mechanical analysis. NMR confirmed the existence of diblock copolymers consisting of 58 mol% PHB as the short chain length block with 42 mol% PHHx as the medium chain length block. The block copolymers had two glass transition temperatures (Tg) at 2.7°C and −16.4°C, one melting temperature (Tm) at 172.1°C and one cool crystallization temperature (Tc) at 69.1°C as revealed by differential scanning calorimetry (DSC), respectively. This is the first microbial short-chain-length (scl) and medium-chain-length (mcl) PHA block copolymer reported. Conclusions It is possible to produce PHA block copolymers of various kinds using the recombinant Pseudomonas putida KT2442 with its β-oxidation cycle deleted to its maximum. In comparison to a random copolymer poly-3-hydroxybutyrate-co-3-hydroxyhexanoate (P(HB-co-HHx)) and a blend sample of PHB and PHHx, the PHB-b-PHHx showed improved structural related mechanical properties.